The Impact of Guest Lectures on the Employability Skills of Satya Terra Bhinneka University Students - Fani Agustriani; Mahlian Elyana; Zulfahmi Syahputra Nasution; Zulfa Hazimah; Indra Hermawan (International Journal of Multidisciplinary Sciences and Arts, 2026)
This study aims to analyze the effectiveness of guest lecturse in improving continuous learning in business law courses for students in 2023 in the Entrepreneurship Study Program at Satya Terra Bhinneka University. This study uses a quantitative approach with a quantitative correlational survey method. The quantitative correlation approach is used to determine whether there is a relationship between two or more variables. In this study, data processing was carried out using SPSS version 26.0. The sample of this study was 162 students of the 2023 class of the Entrepreneurship Study Program, Faculty of Economics and Business, Satya Terra Bhinneka University. The research data collection technique used a questionnaire. The analysis prerequisite tests include validity tests, reliability tests, normality tests, linearity tests, hypothesis tests include simple regression analysis. The results of the study show: There is a significant effect of Guest Lectures on Employability skills of students in the 2023 class of the Entrepreneurship Study Program, Faculty of Economics and Business, Satya Terra Bhinneka University by 65%.